Corporate governance and merger performance: learning from the Australian experience - Mohd Hasimi Yaacob,; Norazlan Alias, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Studies on the relationship between ownership structure and firm performance suggest that ownership structure has a significant impact on firm performance . The methodological choice and various merger-related factors have been identified as affecting the magnitude of post-merger returns.This study investigates the influence of corporate governance characteristics on long-term post-merger stock returns performance of acquirers in Australia. The findings reveal that there is evidence of long-term underperformance by Australian acquirers. However, there is limited evidence of inter-group difference in performance. Further analysis finds evidence that the market reacts positively to merger news for acquirers with high concentration of external substantial shareholders, especially in the case of focused mergers. Malaysia may learn from such experience of an Asia Pacific neighbour as it expands and deepens its corporate spheres.